Sonic hedgehog and Zinc finger protein of the cerebellum 2 gene variants in a South African holoprosencephaly cohort - Jansen van Rensburg, Elizabeth (University of Pretoria, 2024)
Dissertation (MSc (Human Genetics))--University of Pretoria, 2024.